Experimental investigation on performance comparison of self excited induction generator and permanent magnet synchronous generator for small scale renewable energy applications. (August 2022) - Krishna, V.B Murali; Sandeep, V.; Murthy, S.S.; Yadlapati, Kishore
Abstract: This paper presents an experimental performance comparison of self-excited induction generator (SEIG) and permanent magnet synchronous generator (PMSG) for renewable energy-based standalone applications. These two generators have gained popularity in constant speed prime mover-driven power generation systems due to their inherent advantages. Many researchers have proposed various configurations with and without power electronics and battery energy storage for SEIG and PMSG systems. In the isolated systems, the maximum generation and load capacities are known and the primary goal is to maintain a constant voltage and frequency across load terminals. In this context, the performance comparison of both generators is needed to identify the simple, viable, and economical solution for a dedicated source and fixed isolated loads. Therefore, an attempt is made on the performance analysis of micro-hydro turbine driven SEIG and PMSG with resistor heating and induction motor driven pump load applications and compared experimentally to identify suitable voltage regulated generator. The proposed study is not employing power electronic based switches for reactive power (VAR) compensation to make the system cost effective with ease of operation. The working procedure and minimum requirements are discussed in detail for the experimental purpose. Keywords - Self-excited induction generator (SEIG), permanent magnet synchronous generator (PMSG), renewable energy sources, power generation, isolated loads, voltage regulation (VR). Highlights: Identification of a suitable generator for small-scale pico hydro applications. Performance of the self-excited induction generator under different loads. Performance of the specially designed permanent magnet synchronous generator. Comparative analysis between SEIG and PMSG under the same experimental conditions.